Chamber's miscellany of useful and entertaining knowledge / edited by Robert Chambers. - Chambers, William, 1800-1883.; Chambers, Robert, 1802-1871. (Tufts University. Tisch Library., 2016)
Volume 7 of 10. ; 1 online resource (10 volumes) : illustrations, portraits.; Volumes 1-5 edited by Robert Chamber; volumes 6-10 edited by William Chambers.; Each section numbered and paged separately.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.